2020
DOI: 10.1002/cptc.202000023
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐pH‐Sensitive Small Molecule Probe Showing a Ratiometric Fluorescence Color Change

Abstract: We synthesized an amphiphilic small molecule 1 by attaching oligo(ethylene glycol) (OEG) and N,N‐diethylamine (DEA) units to a fluorescent dicyanodistyrylbenzene (DCS) core. The molecule is fully soluble in aqueous solution at low pH (pH<4.3) by protonation of the DEA groups; but, above pH 4.3, it self‐assembles to form nanoparticles due to increased hydrophobicity upon deprotonation, leading to a ratiometric fluorescence color change from green emission in the monomeric form (λem,max=538 nm) to red emission i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[85b] Amphiphilic fluorescent dicyanodistyrylbenzene dye 56 was synthesized for pH sensing. [86] Probe 56 is a ratiometric fluorescence sensor that gives a redshift in fluorescence emission while moving from pH 2.0-7.0. The probe was completely soluble in the water below pH 4.3.…”
Section: Other Ph Probesmentioning
confidence: 99%
“…[85b] Amphiphilic fluorescent dicyanodistyrylbenzene dye 56 was synthesized for pH sensing. [86] Probe 56 is a ratiometric fluorescence sensor that gives a redshift in fluorescence emission while moving from pH 2.0-7.0. The probe was completely soluble in the water below pH 4.3.…”
Section: Other Ph Probesmentioning
confidence: 99%
“…Named after the physicist John Tyndall, TE is a type of light scattering that takes place when visible light is passed through a colloidal solution with a particle size distribution that lies in the 400 to 750 nm range 21 . This phenomenon has already been used as a visual screening method to detect microprecipitates in blends of parental drug solutions 22,23 as well as to evaluate nanolevel aggregation and characterise colloidal catalyst and functional materials [24][25][26][27] . More recently, Xiao et al 28 added quantitative character to a TE-based colorimetry approach and demonstrated a ca.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous online monitoring of pH is considerably significant for bioprocess and environment [ 11 ]. Until now, small molecule probes have been developed to monitor pH using ratiometric fluorescence changing with broad pH response over a range of 1.0 pH unit [ 12 , 13 ]. Several QD-based pH sensors using ratiometric fluorescent sensing have been reported, in which organic dyes were chemically conjugated with QDs as internal reference [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%